2018
DOI: 10.3390/tropicalmed3010026
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Modes of Melioidosis in Taiwan

Abstract: In Taiwan, melioidosis is an emerging disease that suddenly increased in the Er-Ren River Basin, beginning in 2005 and in the Zoynan region during 2008–2012, following a typhoon. Additionally, the disease sporadically increased in a geography-dependent manner in 2016. Subcutaneous inoculation, ingestion, and the inhalation of soil or water contaminated with Burkholderia pseudomallei are recognized as the transmission modes of melioidosis. The appearance of environmental B. pseudomallei positivity in northern, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
0
9
0
1
Order By: Relevance
“…3,4 Risk factors for infection are diabetes mellitus, heavy alcohol consumption, renal disease, chronic lung disease, thalassemia and immunocompromised patients on chemotherapy or prolonged corticosteroid used. 3,4 Risk factors for our patient were occupation as a farmer and diabetes mellitus. We believe that the most probable mode of transmission in our patient was hematogenous dissemination, which can be either from ingestion, inoculation or inhalation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Risk factors for infection are diabetes mellitus, heavy alcohol consumption, renal disease, chronic lung disease, thalassemia and immunocompromised patients on chemotherapy or prolonged corticosteroid used. 3,4 Risk factors for our patient were occupation as a farmer and diabetes mellitus. We believe that the most probable mode of transmission in our patient was hematogenous dissemination, which can be either from ingestion, inoculation or inhalation.…”
Section: Discussionmentioning
confidence: 99%
“…2 People working in the agricultural field, especially farmers, are at a higher risk of being infected, as the bacteria is commonly found on the surface of water and soil. 3,4 Risk factors for infection are diabetes mellitus, heavy alcohol consumption, renal disease, chronic lung disease, thalassemia and immunocompromised patients on chemotherapy or prolonged corticosteroid used. 3,4 Risk factors for our patient were occupation as a farmer and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…66 More recently in Taiwan, as mentioned above, the appearance of a northwesterly wind in a hot spot indicated that airborne transmission had occurred. 67 Exposure to soil or water, particularly during the monsoon season, has been well established to correlate with increased cases of melioidosis. 63 Although melioidosis is not contagious, with human-tohuman transmission rarely reported, 68,69 outbreaks have been linked to unchlorinated water supplies in Australia 70 and from drinking water in rural areas of south/southeast Asia.…”
Section: Routes Of Infectionmentioning
confidence: 99%
“…Melioidosis is an infectious disease caused by a Gram-negative bacterium, Burkholderia pseudomallei, found in soil and water. 1 Three forms of infection have been documented; subclinical, acute and chronic. 2 Acute melioidosis is defined as an illness with symptoms lasting less than two months.…”
Section: Introductionmentioning
confidence: 99%